World Distribution of Heterobostrycus aequalis Waterhouse (Coleoptera: Bostrychidae). - Md Azmi, Mohd Shahman; Abood, Faizah; Ahmad Razi, Norhisham (Academic Journals, 2011)
Heterobostrychus aequalis is a major pest of seasoned hardwood. It attacks many timber and wood from other plant species and caused damage to a broad range of wood products. Their attacks are confined to starch-rich sapwood and often unsuspected until the emergence hole and frass is produced. The repeated introduction of this pest into new areas indicates that it is poorly inspected and ignored. In some cases, this species succeed in establishing its population in the wild. Hence, by providing the world wide distribution of this pest could be the pioneer step in developing better prevention, monitoring, quarantine and control programmes. From the review, it was found that H. aequalis distribute dominantly in tropical and sub-tropical areas. It is widely distributed in Asia, particularly Southeast Asia to Oceania, some parts of Africa, Central America and Caribbean region. The distribution map derived indicates the limits of distribution for H. aequalis to be 40° north and south of the equator. The recent reports and records showed that this pest is potentially becoming a high-risk pest and can establish its population whenever the condition is favourable.